Pemanfaatan Data Spasial dalam Edukasi Daya Dukung Lingkungan bagi Siswa SMA Negeri 1 Tilamuta: Membangun Kesadaran Generasi Muda untuk Pembangunan Berkelanjutan - Maryati, Sri; Merlin, Merlin; Mokoginta, Melani; Mayang, Rohmila (Universitas Negeri Gorontalo, 2025)
The decline in environmental carrying capacity due to land use changes and population pressure poses a challenge to sustainable development. Boalemo Regency has diverse physical conditions, making environmental carrying capacity education essential for the younger generation. This activity aims to enhance students' spatial literacy using spatial data. The methods employed include material delivery, thematic map simulations using Geographic Information Systems (GIS), discussions, and evaluations through pre-test and post-test. Evaluation results indicate an improvement in students' understanding, with topographical condition indicators increasing from 5% to 100% and hydrological condition indicators from 15% to 95%. Spatial data simulations have proven effective in enhancing conceptual understanding and students' critical thinking skills. These results contribute to raising environmental awareness among the younger generation to support sustainable development policies.